An analysis of the training programs of the library associations in the Philippines, 1999-2008 a follow-up study - Mendoza, Ethel H.; Faderon, Rosalie B.; Timoteo, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Library associations help educate and empower professionals about the new library development and assist information professionals in providing and invaluable informal setting for information sharing, updating and improving their skills. Thus, the main purpose of this study is to analyze and evaluate the training programs of nine national library associations and provide data that would help explain how these associations go about with their training seminars and conferences.
The nine library associations under study were: Philippine Librarians' Association, Inc. (PLAI), Association of Special Libraries of the Philippines (ASLP), Philippine Public Librarians League (PPLLI) (formerly Public Librarian's Association of the Philippines (PLAP), Philippine Association of Teachers of Library and Information Science (PATLS), Agricultural Librarians' Association of the Philippines (ALAP), Philippine Association of Academic and Research Librarians (PAARL), Philippine Association of School Librarians (PASL), Philippine Group of Law Librarians (PGLL), and Medical and Health Librarians' Association of the Philippines (MAHLAP). A total of 26 past presidents participated in the survey with 56 percent response rate.
The study found out that in 22 topics were discussed in the training programs with organization being the most discussed (19.96). In terms of topics in librarianship, "Management" (53) had the most number while topics on "Users studies" (5) and "Acquisition" (1) got the least number of discussions.
The study also found out that "Topic with relevance to librarianship and that have practical usefulness" ranked as the foremost reason for selection of topics; "Expertise" of the resource person when selecting speakers; "Time needed for the Planning and Seminar Preparations" was the major reason when selecting date for the trainings; and lastly, "affordability" of the place was preferred when selecting venues. Thirteen respondents (50) agreed that they do collaborate and coordinate, and the other thirteen (50) also answered that they do not collaborate and coordinate with other library associations in determining topics to focus on. 16 new topics were discussed in the training programs conducted within the years 1999-2008 that were not covered in Correo's study that include the broad topics on: 1)Profession; 2) Libraries and Information Centers; 3) Materials; 4) Library Buildings; 5) Bibliographic Control; 6) Bibliographic Records; 7) Computerized Information Storage and Retrieval; 8) Media; 9) Library and Information Science Education; 10) Reading; 11) Knowledge and Learning; 12) Records Management; 13) Archival Management; 14) Health; 15) Ethics; and 16) Law.
Recommendations included are the following : As disseminators of knowledge and new learning, library associations should constantly collaborate/coordinate with each other to provide a wide variety of topics to focus on; there should be a systematic way of organizing associations' documents; PLAI, as the mother association in the Philippines, should be more proactive in developing programs for the library professions. They should provide training programs that their members can participate in regardless of their nature of work.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library science -- Philippines -- Societies, etc; Librarians -- Training of -- Philippines